2016
DOI: 10.4102/ojvr.v83i1.1068
|View full text |Cite
|
Sign up to set email alerts
|

Identification of <i>Echinococcus granulosus</i> strains using polymerase chain reaction–restriction fragment length polymorphism amongst livestock in Moroto district, Uganda

Abstract: A descriptive study was conducted to identify the different strains of Echinococcus granulosus occurring in livestock in Moroto district, Uganda. Echinococcus cysts from 104 domestic animals, including cattle, sheep, goats and camels, were taken and examined by microscopy, polymerase chain reaction with restriction fragment length polymorphism and Sanger DNA sequencing. Echinococcus granulosus genotypes or strains were identified through use of Bioinformatics tools: BioEdit, BLAST and MEGA6. The major finding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Under optimal conditions, the LAMP-LFD protocol was completed within 40 minutes at 63 °C, with easy naked-eye detection of results within 5 minutes. e overall time spent completing the test was faster than that previously reported [14,21]. e specific FITC-labeled probe designed and used in this study to detect LAMP products using LFD confirmed superior specificity in the detection of LAMP reaction products.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Under optimal conditions, the LAMP-LFD protocol was completed within 40 minutes at 63 °C, with easy naked-eye detection of results within 5 minutes. e overall time spent completing the test was faster than that previously reported [14,21]. e specific FITC-labeled probe designed and used in this study to detect LAMP products using LFD confirmed superior specificity in the detection of LAMP reaction products.…”
Section: Discussionsupporting
confidence: 56%
“…Agarose gel-based PCR assays [11,12] and real-time PCR (RT-PCR) techniques [13,14] have been developed and adopted for molecular detection and genotyping of E. granulosus infection in livestock. But these techniques are laboratory-based and costly, thus unsuitable and inapplicable for most low-income countries with low-resource settings where cystic echinococcosis is endemic [15].…”
Section: Introductionmentioning
confidence: 99%
“…The LAMP assay developed by Ni et al has been used for detecting E. multilocularis [21] in wastewater in China [47]. Interestingly, in the work by Ni et al [48], DNA was isolated with the QIAamp DNA Stool Mini Kit which in our hands did not produce satisfactory results. However, the results using the commercial kit were better than using NaOH-based method directly in faeces.…”
Section: Discussionmentioning
confidence: 84%
“…The selection of these regions was based on the predominance of the pastoral production system (Karamoja subregion) or mixed crop-livestock production systems (Eastern and Central subregions), where there is a high prevalence of CE in humans (Magambo et al [ 5 ]), livestock (Chamai et al [ 4 ]), and dogs as previously reported (Inangolet et al [ 6 ] and Oba et al [ 7 ]). These are remote, hard to reach communities with poor health infrastructure and with no specific control programs for CE.…”
Section: Methodsmentioning
confidence: 99%
“…In Uganda, the prevalence of CE has been found to vary between pastoral and agropastoral communities, with pastoral communities being at higher risk than agropastoral communities (Othieno et al [ 3 ]). High prevalence of CE has equally been reported in livestock (Chamai et al [ 4 ] and Magambo et al [ 5 ]) and in dogs (Inangolet et al [ 6 ] and Oba et al [ 7 ]). Cystic echinococcosis is caused by a species of Echinococcus, namely, Echinococcus granulosus, whose definitive hosts are the carnivores such as dogs.…”
Section: Introductionmentioning
confidence: 99%